The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jum.14680
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Ultrasound in Peninsular Arab Patients With Sickle Cell Disease

Abstract: This study has demonstrated the rarity of abnormal transcranial Doppler findings among Peninsular Arab patients with SCD. The guidelines for transcranial Doppler screening in this population need further studies and recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
2
15
1
Order By: Relevance
“…Ashley-Koch et al showed that the US incidence of median survival by genotype was higher in females than in males with SCD [11]. However, Adekile A et al showed, no consistent differences in TCD velocity between male and female patients or in patients with different HbS genotypes [28]. In the current study, the correlation of HbS genotypes with TCD velocities, which in turn correlate with risk of cerebrovascular events, was not significant.…”
Section: Discussioncontrasting
confidence: 61%
“…Ashley-Koch et al showed that the US incidence of median survival by genotype was higher in females than in males with SCD [11]. However, Adekile A et al showed, no consistent differences in TCD velocity between male and female patients or in patients with different HbS genotypes [28]. In the current study, the correlation of HbS genotypes with TCD velocities, which in turn correlate with risk of cerebrovascular events, was not significant.…”
Section: Discussioncontrasting
confidence: 61%
“…In our present and previous studies, we did not encounter any individual with TAMxV higher than 170 cm/s. Indeed, the highest TAMxV was 145 cm/s in the MCA of one SCD patient, while the lowest was 65 cm/s in another patient also in the MCA without MRI evidence of stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation of the CNS involvement showed mostly normal transcranial Doppler values among the patients [49]. Indeed, in a collaborative study with other countries in the region (Oman, Iraq, and UAE), transcranial Doppler values were generally normal [50]. It was also shown that silent brain infarcts are seen in about 3% of Kuwaiti children with SCD, while in adults, the prevalence is ∼20% [51,52].…”
Section: Scd In Kuwaitmentioning
confidence: 95%